Mapping the results of management accounting research in Indonesia - Ratnaningrum Ratnaningrum; Lyna Latifah; Suyanto Suyanto; Y. Anni Aryani; Doddy Setiawan (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2018)
During this time, the publication of the management accounting research is still left behind that of financial accounting. Moreover, there is no description of the previous literature about the causes and effects of management accounting practices in Indonesia. This study aims to describe the accounting management practices in Indonesia by mapping the results of empirical research to answer the questions in each study on what is being observed, what is the direction, what is the type of relationship, and to what level the analysis is. The data collection method used is by mapping the theories which are consistent with the empirical study on management accounting. There are 31 articles which are taken from the accredited national journals and can be tracked online from 2005 to 2017. This study shows that the result of management accounting research consists of four maps. These four maps cover the causes and effects of individual level budgeting; causes and effects of subunit and organizational level budgeting; information for planning and control; performance measures and incentives. The maps with absolutely no research result are: the map of management accounting changes, contract and control: micro processes, individual judgments and decisions, management accounting in historical and social context, organizational change and relation of financial and operational reality. Based on the result, it can be concluded that accounting management research in Indonesia is only restricted on certain topics, especially in the topic of information for planning and control.